(3HZjI GdhYGI aj WHbGJ GddZhjjf hGdfMGIs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s
(3ChdgG (B:s
(3JHOC HJQLeI eMeO Hf Ydi Hf YeQ Hf jMji GdZSGfi , CHj YHO Gddg , GdeYQha HGHf GdYQHi , Hbhdg (B: (3bGd ai JGQjN ZQfGWI cGf ef Cgd GdYde hGdOjf hGdaVd dg YfGjI HGdYQHjI hGdbQGAGJ s
(3BNQgG (B:s
(3JfJgi HJQLeI Ydi Hf jhSa Hf EHQGgje , CHj GdMSf GdbaWi , bhdg (B: (3jYQa HGdbGVi GdCcQe UGMH JGQjN GdfMGI bGd jGbhJ (B: (3hdO ai QHjY SfI KeGf hSJjf hNeS eFI HbaW hcGf SeM Gdca , Wdb GdhLg , Ufa GdCUdGM ddNdd GdhGbY ai GdUMGM ddLhgQi s
(3HgG WjGQGJs
(3fSNI KGfjIs
(3cJHJ Hbde eged GdfbW CMjGfkGs
(3hGdUaMI GdChdi hGdCNjQI HNW eJCNQ hChQGbgG eVWQHI GdJQJjH s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GdJGQjNs